2021
DOI: 10.5056/jnm20086
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Wheat Sensitivity in Irritable Bowel Syndrome and Healthy Subjects: Prevalence of Celiac Markers and Response to Wheat-free Diet

Abstract: Background/AimsMost patients with irritable bowel syndrome (IBS) report food-related aggravation of symptoms. Wheat/gluten is one of the most commonly incriminated. We studied the prevalence of self-reported wheat sensitivity in patients with IBS and in a healthy population from a region in India consuming mixed-cereal diets, correlated it with serological and human leukocyte antigen (HLA) markers of celiac disease, and evaluated the response to a wheat-free diet. MethodsWe surveyed 204 patients with IBS and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…These data were extracted from the annex to a pro forma designed for a prospective observational survey to determine the prevalence of self‐reported wheat sensitivity in a normal population and a cohort of patients with IBS. 18 A total of 400 healthy subjects obtained by convenience sampling and 204 consecutive consenting patients with IBS participated in the survey.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data were extracted from the annex to a pro forma designed for a prospective observational survey to determine the prevalence of self‐reported wheat sensitivity in a normal population and a cohort of patients with IBS. 18 A total of 400 healthy subjects obtained by convenience sampling and 204 consecutive consenting patients with IBS participated in the survey.…”
Section: Methodsmentioning
confidence: 99%
“…There are data available on lactose intolerance from the Indian subcontinent 17 . We have recently reported our data on self‐reported wheat sensitivity among healthy Indian subjects and patients with IBS 18 . In rural northern India, vegetarianism has been reported as a risk factor for IBS symptoms, possibly related to the high content of FODMAPs, including milk products, in the vegetarian diet 19 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among outpatients referred for digestive endoscopy in Italy, 20% reported self-diagnosed NCWS, more frequently female individuals and younger patients [ 4 ]. An Indian study showed that 11.3% of 204 patients with irritable bowel syndrome (IBS) and none of 400 healthy controls self-reported wheat sensitivity, and all IBS patients reported clinical improvement after 6 weeks of GFD [ 5 ]. Likewise, self-reported NCWS was found in 33.6% of Korean patients with IBS, most frequently complying of bloating, abdominal discomfort, and belching [ 6 ].…”
Section: Epidemiology Of Self-reported Nonceliac Wheat Sensitivitymentioning
confidence: 99%
“…Gluten-free diets, once a medical necessity for individuals with celiac disease, have become increasingly popular among the general population, leading to a surge in the demand for gluten-free foods, particularly bread [1][2][3][4][5]. However, a common critique of commercial gluten-free breads is their compromised nutritional quality when compared to their gluten-containing counterparts [6].…”
Section: Introductionmentioning
confidence: 99%